2009
DOI: 10.1111/j.1365-2958.2009.06911.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell elongation and branching are regulated by differential phosphorylation states of the nuclear Dbf2‐related kinase COT1 in Neurospora crassa

Abstract: SummaryDysfunction of the Neurospora crassa nuclear Dbf2-related kinase COT1 leads to cessation of tip extension and massive induction of new sites of growth. To determine the role phosphorylation plays in COT1 function, we mutated COT1 residues corresponding to positions of highly conserved nuclear Dbf2-related phosphorylation sites. Analyses of the point-mutation cot-1 strains (mimicking non-and constitutively phosphorylated states) indicate the involvement of COT1 phosphorylation in the regulation of hyphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 48 publications
3
67
0
Order By: Relevance
“…We and others have shown that the in vivo function of Cbk1 and closely related kinases requires phosphorylation at the HM site (29,45,71), consistent with the broad importance of this regulatory mechanism among AGC kinases. However, the role this phosphorylation plays in the cell is unclear.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We and others have shown that the in vivo function of Cbk1 and closely related kinases requires phosphorylation at the HM site (29,45,71), consistent with the broad importance of this regulatory mechanism among AGC kinases. However, the role this phosphorylation plays in the cell is unclear.…”
Section: Discussionmentioning
confidence: 83%
“…Like other AGC family kinases, Cbk1 is controlled by two key phosphorylations: one in the kinase activation loop (Tloop), and another within a highly conserved C-terminal hydrophobic motif (the HM site, alternatively referred to as the CT motif) (29,45,52,60,71). Cbk1's T-loop modification, by intramolecular autophosphorylation, strongly activates the kinase but is only partially required for function.…”
mentioning
confidence: 99%
“…In Neurospora crassa, hyphal cells are multinucleate (Ramos- Garcia et al 2009) and grow in bifurcating branches (Ziv et al 2009) that can undergo cell-to-cell fusion (Steinberg 2007;Aldabbous et al 2010). Fusion is a dynamic process that occurs by hyphal-cell recognition through a MAPK-dependent sensing mechanism (Fleissner et al 2009).…”
Section: The Filamentous Growth Responsementioning
confidence: 99%
“…COT-1 has been localized to several intracellular compartments, including the cytoplasm and nucleus, and in association with the plasma membrane and various proteins (18,19,54). The role that COT-1 plays in the formation of branched cellular structures as well as its cellular localization has been suggested to be preserved throughout evolution (54,77). Similar conservation may also exist among DBF-2 and its orthologs, of which human LATS1 and Drosophila melanogaster WTS/LATS are, by far, the most extensively analyzed (13,45,53,74,75).…”
mentioning
confidence: 99%